APPLICATION OF THE EQUIVALENCE PRINCIPLE TO THE CALCULATION OF EDUCATION INSURANCE PREMIUMS FOR VILLAGE-OWNED ENTERPRISES (BUMDes) - Widana, I Nyoman; Suciptawati, Ni Luh Putu; Sulma, Sulma (PATTIMURA UNIVERSITY, 2024)
Program Education plays a vital role in improving human resources. But on the other hand, education costs are not cheap. For this reason, people need to prepare education funds from an early age. One way is to take part in an education insurance program. This is a business opportunity that a village-owned enterprise (BUMDes) can run by offering education insurance services to the public. This research aims to develop and use programming software to calculate education insurance premiums offered by BUMDes. The method used is The Equivalence Principle method. Based on the case study, the premium price calculated using software that has been developed is very competitive – below market price, depending on the interest rate and fees charged.